Romanticising crisis: digital revolution and ecological risk in late postmodern American fiction - Traub, C (2015)
This thesis probes how recent experimental American "crisis fictions" from authors including Mark Z. Danielewski, Kathryn Davis, and Evan Dara reformulate transatlantic Romantic literary debates about technological and environmental change. Arguing that such texts extend previously theorised ties between Romanticism and postmodernism, it identifies enduring ties between late-postmodern accounts of crisis and those of Romantic predecessors. Responding to the upheavals of digital revolution and ecological risks, these texts, published between 1995 and 2012, inventively engage several linchpin constructs in transatlantic Romantic writing: chiefly, the imagined supersession of subjective and temporal boundaries; a sense that the natural and non-human world is of crucial importance; and a reliance on idioms of sublimity to suggest the unrepresentability of the aforementioned crises. Although numerous critics have traced similarities between Romantic and postmodern modes, this thesis considers those resonances as deeper questions of cultural and literary history. It proposes to more carefully historicise the Romantic intellectual heritage in late postmodernism, identifying intermediating moments that inform contemporary accounts of crisis. It unearths how late postmodern technocultural and environmentalist imaginaries were always already Romantic. Deeply informed by countercultural, mid-century American movements and ideas that themselves drew significantly from transatlantic Romanticism, contemporary figurations of upheaval, syncretically figured in mid-century publications such as the Whole Earth Catalog, are indebted to both Romantic and neo-Romantic heritages. This thesis additionally argues that the digital revolution and unprecedented environmental crisis act as pressures on postmodern literary practices from the mid-1990s onward. Digital speeding and a looming sense of ecological risk register as even earlier crises than the terrorist attacks of "9-11", requiring a recalibration of what the postmodern might mean and do. Crucially, in their preoccupation with embodied realities and environments, including natural ones, the contemporary narratives examined here diverge from the assumption that the natural world bears little importance in postmodern fields of representation. Finally, many recent literary experiments figure themselves as materially participating in the technological and medial systems they respond to; formal experimentation is, accordingly, another centre of interest. This research examines how select texts deploy formal strategies to "materially instantiate" Romantic ideas, to borrow Katherine Hayles's term. Although numerous critics have suggested that Romantic discourse permeates digital cultural imaginaries, existing scholarship devotes little attention to how formal experimentation intersects with narrative strategies.